Expression of estrogen and progesterone receptor genes in endometrium, myometrium and vagina of postmenopausal women treated with estriol - Bryś, Magdalena; Szyłło, Krzysztof; Romanowicz-Makowska, Hanna; Dobrowolski, Zbigniew; Masłowska, Izabela; Krajewska, Wanda (São Paulo Medical Journal, 2009)
CONTEXT AND OBJECTIVE: Estriol is an estrogen with considerably weaker stimulatory effects on endometrial proliferation than estradiol. A study was conducted to determine the level of estrogen receptors (ERs) and progesterone receptors (PRs) in women who received 14-day vaginal estriol therapy, compared with those who did not receive this therapy. ER and PR gene expression was analyzed in the endometrium, myometrium and vagina of postmenopausal women treated with estriol. DESIGN AND SETTING: Analytical cross-sectional study, at the Research Institute of the Polish Mothers’ Memorial Hospital, Lodz, Poland. METHODS: Twenty-seven postmenopausal women (57-74 years of age) were included in the study. All of them were waiting for per vaginam hysterectomy or plastic surgery on the vagina and perineum because of uterine prolapse. ER and PR gene expression was determined by means of the technique of reverse transcription polymerase chain reaction (RT-PCR). RESULTS: In the estriol-treated patients, in comparison with the control group, a significant increase in ER gene expression was observed in the endometrium and vagina, while enhanced PR gene expression was found in the endometrium. However, under histological examination of the endometrium, estrogen stimulation of low and medium degree was diagnosed for 21.4% and 14.3% of the estriol-treated women, respectively. CONCLUSION: The results obtained suggest that the women who received 14 days of treatment with vaginal estriol had higher ER and PR mRNA levels. No difference between these groups regarding endometrial proliferation was observed.